Explorando a ocorrência de Soldadinhos (Hemiptera: Membracidae) no estado de São Paulo, a partir de dados da plataforma iNaturalist. - Stefanuto, André Mateus Rodeguero [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The treehoppers are the Membracidae family. These small Hemipterans have great diversity of species in the Neotropics. They have a structure called “pronotum”, which presents many different shapes related to the Natural History of each species. Its taxonomy and diversity are well researched, but the group lacks of many ecological studies. They are closely related with a wide variety of plants and, as a result, considered ecological indicators of the environment. Sampling. Documenting the group diversity in large geographic areas is a task facilitated by Citizen Science. This worked aimed to know and model the occurence of Membracidae family in São Paulo state using observations made by citizen scientists through iNaturalist. The exploratory analysis of the data was done using QGIS and Rstudio and the modelling was carried out by MaxEnt. The results shows more observations in vegetation fragments close to urban areas, mainly where there is greater populational – and citizens scientists – density. Also, the species diversity is greater inside vegetation fragments and smaller in urban areas. The modeling points to a certain preference of treehoppers for areas with more stable temperature and high water availability/rainfall index, subject to the limitations of the results. Thus, covering a large temporal and spatial scale of the records, this work contributes to the understanding of the habitats occupied by the Membracidae family.

Os soldadinhos compõem a família Membracidae, pequenos Hemípteros com grande diversidade nos neotrópicos. Possuem uma estrutura chamada “pronoto”, que apresenta formas bastante diversas e intimamente relacionadas à História Natural das espécies. Sua taxonomia e diversidade é bastante estudada, mas o grupo ainda carece de muitos estudos ecológicos. Os membracídeos se associam intimamente a uma grande variedade de organismos vegetais e por isso são considerados indicadores ecológicos de ambientes. Documentar a diversidade de soldadinhos em grande escala geográfica é uma tarefa facilitada pela Ciência Cidadã. Este trabalho buscou conhecer e modelar a ocorrência desta família no estado de São Paulo utilizando registros feitos por cidadãos cientistas através da plataforma iNaturalist. A exploração da ocorrência foi feita utilizando os programas QGIS e Rstudio e a modelagem foi realizada pelo programa MaxEnt. Os resultados mostram registros mais abundantes nas proximidades de fragmentos vegetacionais no entorno de áreas urbanas, onde há maior concentração populacional - e de cidadãos cientistas. Também foi possível notar maior diversidade de espécies em áreas vegetadas e menor em áreas urbanas. A modelagem aponta para possível preferência de Soldadinhos por regiões com temperaturas mais estáveis e com alta disponibilidade hídrica/pluviosidade, guardadas as imitações dos resultados. Assim, abrangendo grande escala temporal e espacial dos registros, este trabalho contribui para o entendimento dos habitats ocupados pela família Membracidae.
Exploring the treehopper occurrence (Hemiptera: Membracidae) in the state of São Paulo, based on data from the iNaturalist platform.
Keywords: Ecologia animal; Insetos florestais; Participação do cidadão